Here, there and everywhere: a study of consumer centrism - Prince, Melvin; Davies, Mark; Cleveland, Mark; Palihawadana, Dayananda (International Marketing Review, 2016)
Purpose - A first objective is to add insight into how constructs of ethnocentrism, xenocentrism and cosmopolitanism relate to each other. Knowledge of how these constructs overlap or work together in affecting consumer preferences will offer global marketers insights for designing appropriate marketing strategies. The second objective is to extend this knowledge by examining the correspondence of these three constructs to a nomological network of dispositional concepts pertinent for product positioning and market segmentation. The third objective is to empirically examine the extent to which the measures, construct structure and associative relationships are robust in different national research settings. The paper aims to discuss these issues. Design/methodology/approach - Surveying British and American consumers, this study examines and analyzes the correspondence of these identity-relevant constructs within a nomological net of pertinent concepts: consciousness-of-kind, global consumption orientation, materialism and natural environment concern. Findings - The hypothesized negative links between CET-XEN and CET-COS, and the predicted positive connection between XEN-COS were all confirmed on the latent factor results for the combined data set. The negative correlation between CET-XEN was of a considerably lower magnitude than that for CET-COS. Originality/value - To date, no research has used an identity theory framework and simultaneously examined in a cross-cultural context the interrelationships of consumer ethnocentrism consumer xenocentrism and cosmopolitanism - and their differentiating linkages to a multiplicity of consumer dispositions.
Keywords: Cross-cultural studies; Ethnocentrism; Global marketing; Green issues; Market segmentation; Marketing; dept.mkt; peer-reviewed

Here, There and Everywhere: The Polycentric Consumer - Cleveland, Mark; Prince, Melvin (Springer International Publishing, 2016)
Identity is recognized as a powerful antecedent of behavior. Social identity denotes the incorporation of culture into a person’s self-concept. A strong correspondence exists between identity with a given social unit and commitment to group values/norms, and thus, how much influence the social unit exerts on the person’s attitudes and behaviors. As a psychological construct, social identity research requires probing how individuals subjectively interpret their own affiliation with one or several collectivities. Cultures are increasingly emancipated from geography in the global era. Because contemporary consumers are continuously exposed to a variety of cultural influences, they may develop polycentric identities. As companies and markets integrate, a key international market segmentation topic relates to consumers’ mindsets about home and extraneous countries/cultures, and subsequently, the products connected with these entities. To date, no research has simultaneously examined the interrelationships of consumer ethnocentrism (bias towards products from one’s national culture), consumer xenocentrism (i.e., preference or orientation towards products from a culture other than one’s own), and cosmopolitanism (i.e., a yearning for and adeptness at mastering cultural diversity) in a single study. Employing an online survey, and drawing from a representative sample (n = 269) of American consumers drawn from all 50 states (plus D.C.), this research also examines the correspondence of these identity-relevant constructs within a nomological net of pertinent concepts (all of which are established in the marketing literature): materialism, consciousness-of-kind, external orientation (cultural open-mindedness and consumption of foreign media), global consumption orientation, and natural environment concern. The survey contained a total of 60 scales corresponding to the 8 constructs, along with a series of key demographic measures. Exploratory and confirmatory factor analyses were applied to the construct measures. Various analytical techniques were employed (tests for convergent/discriminant validity, bivariate correlations, t-tests, MANOVA, two-step clustering, as well as path analyses using structural equation modelling) to test the 19 proposed theoretical hypotheses. Most hypotheses were supported, in terms of statistical significance and magnitude, as well as directional valence. Associative network memory theory and signaling theory implicate how consumers decide from a constellation of local, foreign, and global product options. Upon activation of a brand node by way of retrieval cues (product categories, brand names, and so forth), linkages such product attributes and semantic associations (e.g., ingroups/outgroups and corresponding levels of felt identification) become salient. Firms can manipulate signals, including associations towards or away from countries/cultures, to position products and persuade consumers. Vertical segmentation, the conventional approach to adapting marketing strategies, entails developing marketing mixes for each country, from the near limitless combination of demographic, economic and psychographic variables. Due to the globalization of media and the widespread movement of products and peoples across borders a growing number of researchers instead advocate horizontal segmentation, whereby similar groups of consumers are targeted with an essentially uniform marketing strategy, irrespective of where they might live. Individuals’ inward and outward dispositions—towards their own and different countries, cultures, and products—are sound candidate constructs for designing horizontal strategies.
Keywords: Consumer Ethnocentrism; External Orientation; Foreign Medium; Semantic Association; Social Unit; dept.mkt

An integrative framework of buyer-supplier negative relationship quality and dysfunctional interfirm conflict - Prince, Melvin; Palihawadana, Dayananda; Davies, Mark A. P.; Winsor, Robert D. (Journal of Business-to-business Marketing, 2016)
Purpose: Problems of relationship quality and interfirm conflict in business-to-business settings are serious concerns that need to be addressed. Thus, the authors have engaged in an extensive review to promote an understanding of these complex issues. This article develops an integrated framework for analyzing wide-ranging relations between individual representatives and patterns of interfirm incompatibility for managerial control.Methodology/approach: The review involves numerous sources that include articles and monographs. A theoretical framework is constructed to integrate fragmented empirical data. In particular, social identity and commitment-trust theories are mobilized for this framework.Findings: The review of studies has a substantial consistency with the theoretical framework. The article outlines a causal chain from interpersonal agent dissimilarities to dysfunctional buyer-supplier relations, culminating in interfirm pathological conflict. Moderating factors in the causal chain are: agent identity differentiation (for interpersonal dissimilarity), supplier relations mismanagement (for buyer-supplier relationship quality), and interfirm opportunism (for interfirm pathological conflict). Buyer-supplier interfirm incompatibility mediates the causal link between interpersonal dissimilarity and buyer-supplier relationship quality. Identity differentiation, the validation of one's self-image, is introduced as a process that determines buyer-supplier agent interpersonal dissimilarity judgments. This framework uses a contextual perspective. It describes interactions between observations of micro-level phenomena of interpersonal dissimilarities and macro-level models of interfirm fit. From a managerial perspective, interpersonal relations between individual buyer and supplier agents may be further strengthened by such strategies as expanding the scope of the interpersonal relationship, relaxation of role responsibilities, and volunteering business-related contact referrals.Originality/value: A new theoretical framework has been devised to predict and explain relationship quality and interfirm pathological conflict in the business-to-business context. The framework contributes to the value of the knowledge base by serving as a means for building new diagnostic tools for assessment of interfirm behavioral issues affecting exchanges. New concepts are introduced to enhance current literature on business-to-business marketing. The framework provides concreteindicators that operationally define ideas and enable or improve measurement for empirical modeling.
Keywords: business marketing; dept.mkt; industrial marketing; relationship quality; similarity; supplier compatibility